Twenty-four hour variability of inverted T-waves in patients with apical hypertrophic cardiomyopathy - Ma, Fei; Yang, Yating; Tao, Jingwen; Deng, Xiaoyan; Chen, Xufeng; Fan, Jingjing; Bai, Xuelei; Dai, Tongyu; Li, Sheng; Yang, Xiaoyun; Lin, Fan (Frontiers in Cardiovascular Medicine, 2022)
Background: Patients with apical hypertrophic cardiomyopathy (ApHCM) have marked inverted T-waves that vary over several years. Inverted T-waves in ApHCM are unstable, but it is unclear whether this change is due to coronary artery disease (CAD) or if it is a characteristic of ApHCM itself. We aimed to study the characteristics of inverted T-waves in patients with ApHCM over the course of 24 hours to improve the diagnostic indices of ApHCM. Methods: We examined 83 patients with ApHCM and 89 patients with CAD (who served as the control group). All patients underwent a 24-hour dynamic electrocardiogram (ECG). We analyzed the average depth of inverted T-waves per minute and sorted them from shallow to deep; the sorted ECG segments at the 10th, 50th, and 90th positions of the T-wave were subsequently analyzed. Results: The amplitudes of inverted T-waves in ApHCM corresponding to the 10th, 50th, and 90th percentile were -5.13 ± 4.11 mm, -8.10 ± 4.55 mm, and -10.9 ± 5.04 mm, respectively. Changes in the degree of inverted T-waves were greater in ApHCM than in CAD. T-wave amplitudes in ApHCM were strongly associated with heart rate and circadian rhythm and only weakly associated with CAD and posture. Maximum T-wave amplitudes in the CAD group were < 10 mm, while 68% of patients with ApHCM had maximum T-wave amplitudes > 10 mm, and all patients with ApHCM aged < 50 years had maximum T-wave amplitudes > 10 mm. Conclusions: Notable variations in the T-waves of patients with ApHCM were observed over 24 hours. ECG examinations during states of inactivity (comparable to sleep) improved the sensitivity of the diagnosis of ApHCM. Inverted T-wave amplitudes correlated with heart rate and circadian rhythm, where T-wave changes in ApHCM may be due to the normalization of abnormal T-waves effect. Identifying T-wave amplitudes > 10 mm can effectively improve the diagnostic rate of ApHCM, especially in patients aged < 50 years. The short-term change in T-waves in patients with ApHCM could become the novel index that will help in the diagnosis of ApHCM.